P1-S1.39 Azithromycin susceptibilities in Canadian Neisseria gonorrhoeae isolates (2006–2010). (10th July 2011) - Sawatzky, P; Martin, I; Allen, V; Hoang, L; Lefebvre, B; Lovgren, M; Gilmour, M
Abstract : Background: Canada conducts surveillance of antimicrobial susceptibilities in Neisseria gonorrhoeae strains to support development of treatment guidelines. Methods: N gonorrhoeae strains were isolated or collected by Canadian provincial public health and reference laboratories. Minimum inhibitory concentrations (MICs) were determined by agar dilution for penicillin, spectinomycin, tetracycline, erythromycin (ery), ceftriaxone, ciprofloxacin (cip), cefixime, and azithromycin (az) at the provincial laboratories or the National Microbiology Laboratory (NML). Sequence types (ST), auxotypes, and plasmid profiles were also determined at the NML. Results: Thirty-nine strains from British Columbia (n=18), Alberta (n=2), Ontario (n=9) and Quebec (n=10) were found to be az resistant (R) (MIC≥2 μg/ml) by either a provincial laboratory or NML between 2006 and 2010. Ten different resistance profiles were represented by the 39 strains. Twenty or 51.3% were Chromosomally-Mediated Resistant N gonorrhoeae /azR/cipR (CMRNG/azR/cipR), 4 (10.3%) were Probable CMRNG/azR/cipR and 3 (7.7%) were Penicillinase-Producing N gonorrhoeae /Tetracycline-Resistant N gonorrhoeae /azR/cipR/eryR (PPNG/TRNG/azR/cipR/eryR). One strain was CMRNG/azR/cipR with reduced susceptibility to cefixime. Twenty-one different sequence types were determined, the most common being ST-1407 with 20.5% (8/39), ST-225 and ST-4815 with 10.3% (4/39) each. Although the estimated rate of azithromycin resistance between 2006 and 2009 is very low at 0.2% of all isolates tested across Canada (31/15 487), the MICs for azithromycin are gradually increasing. In 2001, the majority of strains (27.8%) had an azithromycin MIC=0.25 μg/ml which increased to 51.5% by 2006. In 2007, the majority of strains (55.9%) had azithromycin MIC=0.5 μg/ml. The highest azithromycin MIC found was ≥64 μg/ml (n=2). Conclusions: A shift in azithromycin MICs has definitely occurred and may continue to increase. Although azithromycin is not recommended as the primary treatment for gonorrhoea, it is listed as an alternative treatment. With the increasing reduced susceptibility of our primary treatments for gonorrhoea (cefixime and ceftriaxone), azithromycin may be required to treat gonorrhoea either on its own or in combination with third generation cephalosporins. Therefore, it is imperative that azithromycin susceptibilities in N gonorrhoeae continue to be monitored.